The Importance of Nodule Size in the Management of Ruptured Thyroid Nodule After Radiofrequency Ablation: A Retrospective Study and Literature Review - Chen, Wen-Chieh; Luo, Sheng-Dean; Chen, Wei-Chih; Chou, Chen-Kai; Chang, Yen-Hsiang; Cheng, Kai-Lun; Lin, Wei-Che (Frontiers in Endocrinology, 2021)
Background: Nodule rupture is a relatively uncommon yet severe complication of radiofrequency ablation (RFA). When nodule rupture occurs, determining suitable therapeutic management is a critical issue. A study herein aimed to identify the predictive factors affecting the management of post-RFA nodule rupture. Methods: Post-RFA nodule rupture data of 9 patients were enrolled from 2 medical centers. A literature investigation was performed, uncovering nodule rupture data of 17 patients. A total of 26 patients were analyzed and divided into two groups, categorized as patients requiring either invasive or conservative therapeutic management. Data including initial symptoms, imaging, therapeutic management, and prognosis were reviewed and compared between the two groups. Results: Significant differences in nodule diameter, and the ablation time of the course prior to rupture (RUP time) were noted between the two groups (p = 0.045 and 0.008, respectively). Logistic regression analysis indicated the initial nodule diameter and RUP time significantly affected the requirement of invasive treatment (OR 1.99 and 1.11, respectively). Considering practicality, when a nodule with an initial maximum diameter of >4.5cm ruptured, invasive management was suggested (sensitivity 69% and specificity 79%). Conclusion: Though nodule ruptures can be managed conservatively, a ruptured nodule with an initial maximum diameter of >4.5cm may require invasive management. Understanding the significant clinical and imaging features will help physicians make an appropriate risk assessment to determine the correct treatment in a timely manner.